Pengembangan Aplikasi Manajemen Turnamen XiangQi Sistem Knockout dan Round Robin PEXI Jambi - Cynthia Navela Sari; Marrylinteri Istoningtyas; Maria Rosario Borroek (Politeknik Caltex Riau, 2019)
PEXI (Persatuan Xiangqi Indonesia) Pengprov Jambi is a united organization for XiangQi athletes especially in Jambi Province. Today, XiangQi tournament system in Jambi has used tournament management application, however it is just limited on Swiss Tournament System. That’s why if the tournament is held with other systems, which are Knockout and Round Robin, the management still uses manual method in determining the tournament pairing and calculation of player’s point. Since the calculation is still done manually, so there are mistakes in calculation player’s points and there are frequently deceptions in determining tournament pairing. Besides, the old application interface is needed to be upgraded in order to be more user-friendly to be used. Therefore, we require a development in system with complete tournament systems and more user-friendly interface to be used..